New Domain Decomposition Method For Quality-Aware Parallel H.264 Video Coding - Aboalmaal, Mohammed Faiz; Abdullah, Rosni; Kattan, Ali (Malaysian Journal of Computer Science, 2014)
In this paper, we present a new parallel granularity called â€œtilingâ€ to parallelize the H.264 codec. The new parallel granularity, which has the same granularity level as the parallel slice-level H.264 codec, is based on decomposing the entire video frame into tiles by utilizing a new inherently parallel 2D domain decomposition method. To assess the proposed approach, its parallel scalability, bit rate, and parallel impact on visual quality (peak signal-to-noise ratio) are compared with those of other approaches. Empirical results show significant improvements in encoding time as compared to the serial and the parallel slice-level approaches. In terms of peak signal-to-noise ratio and bit rate, certain results improved, a few were comparable, while a few were discouraging, when compared to the results of the other approaches. However, addressing the limitations of the proposed method is highlighted as future work.